Model Of Traditional Land Arrangement In Sungayang Village, Tanah Datar Regency, West Sumatra - Azwar; indraddin; Rahmaini , Indah Sari; Anggraini , Retno (Jurnal Sosial Terapan, 2025)
The arrangement of ulayat land in the village is important because it is useful for maintaining the existence of the ulayat land and can also improve the economy and welfare of the village community itself. So the purpose of this study is to develop a model for the arrangement of ulayat land in the village of Sungayang, Tanah Datar Regency, West Sumatra. The study used a qualitative approach by adopting qualitative data collection methods and PRA techniques. Anthony Giddens' structuration theory was used as a research guide. The arrangement of ulayat land cannot only be done with formal rules for land arrangement and registration, but it requires the involvement of local wisdom and local institutions. The initial step needs to be carried out by socializing all elements in the village community such as niniak mamak, alim ulama, cadiak pandai, bundo kanduang and village youth. Socialization will build an agreement in land arrangement. After the agreement is established, the determination of the subject, land object, measurement, land registration, HPL management and land arrangement are carried out. Utilization of ulayat land requires SOP and innovation in increasing yields. Increasing the yield of ulayat land is possible with the issuance of HPL, because it can be collaborated with third parties based on the HPL owned. However, utilization to improve community welfare is the main choice to make the community a business partner in utilizing ulayat land in the village. The role of the village government and the Village Customary Council (customary law community) is very much needed to achieve the goal of utilizing ulayat land in the village.